Prognostic and predictive role of lactate dehydrogenase 5 ( LDH5) expression in colorectal cancer patients treated with PTK787/ZK 222584 (Vatalanib) anti-angiogenic therapy - Koukourakis, Michael I. (2011)
PURPOSE: The CONFIRM randomized trials, investigating the role of the VEGF-receptor inhibitor PTK787/ZK 222584 (vatalanib) in colorectal cancer (FOLFOX 4 ± vatalanib), showed some benefit in patients with high serum LDH levels. Here we investigated the expression of LDH5 (encoded entirely by the LDHA gene, regulated by the hypoxia inducible factors) in cancer tissues from patients recruited in the CONFIRM trials and relationship to response. EXPERIMENTAL DESIGN: Paraffin embedded materials from 179 patients recruited in the CONFIRM trials were analyzed by immunohistochemistry for the expression of the LDH5 protein. Correlations with serum LDH, response and survival were assessed. RESULTS: A significant association of tumor burden and of poor Performance Status (PS) with serum LDH was noted. Poor PS and high tumor LDH5 expression predicted for poor response rates. High tissue LDH5 was related to poor progression free survival (PFS) only in the placebo group of patients, while the addition of Vatalanib seemed to improved response and PFS in this subgroup. High serum LDH levels were linked with significantly poorer overall survival, which however was not sustained in multivariate analysis. CONCLUSIONS: Serum LDH and tissue LDH5 levels are complementary features that help to characterize the activity of lactate dehydrogenase in colorectal cancer and have a potent value in predicting response to chemotherapy. The addition of vatalanib diminished the impact of LDH expression on the prognosis of patients.